Estudo da labilidade de Cu(II), Cd(II), Mn(II) e Ni(II) em substâncias húmicas aquáticas utilizando-se membranas celulósicas organomodificadas - Rosa, André Henrique [UNESP] (2007)
In this work commercial filters papers were organomodified with tetraethylorthosilicate (TEOS) and 3-aminopropyltriethoxysilane (3-APTS), aiming at the development of a new analytical procedure for in-situ speciation of labile and inert metal species in aquatic systems. Parameters that exert influence on the metal lability such as pH, chelating time, concentration and characteristics of the organic matter were studied in the laboratory using tests for metal recuperation. The results showed slower kinetics for Cu ion than for Ni, Mn and Cd in the absence of aquatic humic substances (AHS). The relative lability observed for complexed metals in aquatic humic substances using organomodified filter papers was Cu>>Cd>Ni>Mn. The pH values, structural characteristics and concentration of AHS exert strong influence on the lability of the metals. The results obtained showed that the utilization of organomodified filter papers can be an interesting and promising alternative for in situ characterization of metal lability in aquatic systems.